5.8k views
5 votes
Prove that tan⁴O+ tan²O=sec⁴O-sec²O​

User UpVs
by
4.8k points

2 Answers

4 votes

Answer:

Hi, hope this helps:-)

Prove that tan⁴O+ tan²O=sec⁴O-sec²O​-example-1
User Jamida
by
5.5k points
6 votes

Solution :

To Prove :-

  • tan⁴ θ + tan² θ = sec⁴ θ - sec²θ

Proof :-

So here we would be proving the L.H.S. equal to R.H.S.,

⇒ tan⁴ θ + tan² θ

Taking tan² θ as common,

⇒ tan² θ (tan² θ + 1)

Identity as we know that,

  • sec² θ = 1 + tan²θ

By using it we gets,

⇒ tan² θ (sec² θ)

Now putting sec²θ - 1 in the place of tan²θ,

⇒ (sec²θ - 1) (sec² θ)

⇒ (sec²θ - 1) × (sec² θ)

⇒ sec⁴θ - sec² θ

Hence proved..!!!

Additional Information :

  • sin² θ + cos² θ = 1
  • sin² θ = 1 - cos²θ
  • sec²θ = 1 + tan²θ
  • cot²θ = cosec²θ - 1

Reciprocal identities :-

  • sin θ = 1 / cosecθ
  • cosec θ = 1 / sin θ
  • cos θ = 1 / sec θ
  • sec θ = 1 / cos θ
  • tan θ = 1 / cot θ
  • cot θ = 1 / tan θ

User Soulxy
by
5.3k points